Influence of resistance training variables and the nordic hamstring exercise on biceps femoris architectural adaptations in soccer players: a systematic review - Pecci, J.; Sañudo, B.; Ramirez-Campillo, R.; Saez de Villarreal, E. (Sports Health: A Multidisciplinary Approach, 2025)
Context: Manipulation of resistance training variables influences the structural and functional adaptations of muscle, having a great impact on sport performance and hamstring injury prevention.